(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article explores the transformative impact of artificial intelligence on foreign language learning. It examines how AI-powered tools and platforms are reshaping traditional methods of language instruction by providing personalized, interactive, and adaptive learning experiences. The study focuses on AI applications such as ChatGPT, Duolingo, and ELSA Speak, analyzing their roles in enhancing learners’ speaking, listening, and comprehension skills. Through a literature review, the paper highlights the pedagogical benefits of AI technologies, including instant feedback, customized lesson planning, and increased learner engagement. Special attention is given to the role of natural language processing and speech recognition in creating realistic conversational practice. The article concludes with a discussion of current challenges, ethical considerations, and future prospects for integrating AI into language education.